A hydrophobic barrier deep within the inner pore of the ​TWIK-1 K2P potassium channel - Aryal, Prafulla; Abd Wahab, Firdaus; Bucci, Giovanna; Sansom, Mark; Stephen, Tucker (Nature Publishing Group, 2014)
Recent X-ray crystal structures of the two-pore domain (K2P) family of potassium channels have revealed a unique structural architecture at the point where the cytoplasmic bundle-crossing gate is found in most other tetrameric K+ channels. However, despite the apparently open nature of the inner pore in the ​TWIK-1 ( K2P1/​KCNK1) crystal structure, the reasons underlying its low levels of functional activity remain unclear. In this study, we use a combination of molecular dynamics simulations and functional validation to demonstrate that ​TWIK-1 possesses a hydrophobic barrier deep within the inner pore, and that stochastic dewetting of this hydrophobic constriction acts as a major barrier to ion conduction. These results not only provide an important insight into the mechanisms which control ​TWIK-1 channel activity, but also have important implications for our understanding of how ion permeation may be controlled in similar ion channels and pores.